Analisis Faktor-faktor yang Mempengaruhi Konsumen dalam Pemilihan Kedai Kopi di Kota Denpasar - I KETUT SUAMBA; DWI PUTRA DARMAWAN; NI MADE REIKA PRAMITA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Analysis of Factors Influencing Consumers in Choosing Coffee Shops in Denpasar City. Nowadays, having coffee in coffee shops has become a habit or lifestyle for Indonesian. The increasing coffee consumption in Indonesia is in line with the proliferation of coffee shops in various places, especially in a number of big cities, including Denpasar. Using qualitative and quantitative data, this study aims to determine the profile of coffee shops in Denpasar City and to identify the factors that influence consumers in choosing coffee shops in Denpasar City. 80 respondents were selected through accidental sampling. The study uses Multiple Linear Regression Analysis with consumer decisions as the dependent variable (Y) and price, product quality, promotion, store atmosphere and location as the independent variable (X). Based on the result, the profile of coffee shops in Denpasar was identified. Most coffee shops in Denpasar are still classified as a small business. Coffee shops in Denpasar sell both coffee and non-coffee beverages as well as snacks, such as donuts, toast and others with price ranges between Rp. 15,000 and 35,000. The coffee shops have different concepts, quality of taste, characteristics and provide different facilities, such as wifi, electrical plugs, air-conditioned rooms, smoking areas and so on. The result shows that price, product quality, promotion, store atmosphere and location influence consumer decision in choosing coffee shops in Denpasar. Coffee shop entrepreneurs in Denpasar may consider the above-mentioned variables in improving their business. For instance, they may consider improving the facilities, maintaining the suitability of taste quality with price, using promotions and choosing the right location in opening new shops.